Narciclasine inhibits angiogenic processes by activation of Rho kinase and by downregulation of the VEGF receptor 2. (October 2019) - Bräutigam, Jacqueline; Bischoff, Iris; Schürmann, Christoph; Buchmann, Giulia; Epah, Jeremy; Fuchs, Simone; Heiss, Elke; Brandes, Ralf P.; Fürst, Robert
Abstract: The process of angiogenesis is involved in several pathological conditions, such as tumor growth or age-related macular degeneration. Although the available anti-angiogenic drugs have improved the therapy of these diseases, major drawbacks, such as unwanted side effects and resistances, still exist. Consequently, the search for new anti-angiogenic substances is still ongoing. Narciclasine, a plant alkaloid from different members of the Amaryllidaceae family, has extensively been characterized as anti-tumor compound. Beyond the field of cancer, the compound has recently been shown to possess anti-inflammatory properties. Surprisingly, potential actions of narciclasine on endothelial cells in the context of angiogenesis have been neglected so far. Thus, we aimed to analyze the effects of narciclasine on angiogenic processes in vitro and in vivo and to elucidate the underlying mechanism. Narciclasine (100–300 nM) effectively inhibited the proliferation, undirected and directed migration, network formation and angiogenic sprouting of human primary endothelial cells. Moreover, narciclasine (1 mg/kg/day) strongly reduced the VEGF-triggered angiogenesis in vivo (Matrigel plug assay in mice). Narciclasine mediated its anti-angiogenic effects in part by a RhoA-independent activation of the Rho kinase ROCK. Most importantly, however, the compound reduced the de novo protein synthesis in endothelial cells by approx. 50% without exhibiting considerable cytotoxic effects. As a consequence, narciclasine diminished the presence of proteins with a short half-life, such as the VEGF receptor 2, which is the basis for its anti-angiogenic effects. Taken together, our study highlights narciclasine as an interesting anti-angiogenic compound that is worth to be further evaluated in preclinical studies. Highlights: Narciclasine decreases key features of angiogenesis in cultured endothelial cells. Narciclasine strongly reduces the VEGF-triggered angiogenesis in vivo . The anti-angiogenic action is linked to a RhoA-independent activation of the ROCK. The major mode of action of narciclasine is the reduction of VEGFR2 protein levels. This reduction is based on the inhibition of de novo protein synthesis.